2009
DOI: 10.1016/j.schres.2009.09.021
|View full text |Cite
|
Sign up to set email alerts
|

An examination of neuroticism as a moderating factor in the association of positive and negative schizotypy with psychopathology in a nonclinical sample

Abstract: Personality traits such as neuroticism are associated with schizophrenia and schizotypy. However, studies thus far have not clarified the differential association of neuroticism with individual schizotypy dimensions and the role it plays in the expression of schizophrenia-spectrum psychopathology. 204 nonclinically ascertained participants completed self-report questionnaires assessing neuroticism and the positive and negative schizotypy dimensions, and underwent structured interviews assessing schizophrenia-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
27
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 52 publications
(58 reference statements)
6
27
1
1
Order By: Relevance
“…Quality of life and overall functioning in schizophrenia can be predicted by antecedent risk factors of the illness, such as temperament and personality (Barrantes-Vidal et al, 2009; Boyette et al, 2014b; Compton et al, 2015; Herrán et al, 2006; Kentros et al, 1997; Lahey, 2009; Lysaker et al, 1998). For example, neuroticism and extraversion are associated with quality of life and overall functioning in schizophrenia (Boyette et al, 2014b; Lahey, 2009; Lysaker et al, 1998), and the effect on quality of life persists when controlling for symptoms and sociodemographic factors (Boyette et al, 2014b, 2014a; Kentros et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life and overall functioning in schizophrenia can be predicted by antecedent risk factors of the illness, such as temperament and personality (Barrantes-Vidal et al, 2009; Boyette et al, 2014b; Compton et al, 2015; Herrán et al, 2006; Kentros et al, 1997; Lahey, 2009; Lysaker et al, 1998). For example, neuroticism and extraversion are associated with quality of life and overall functioning in schizophrenia (Boyette et al, 2014b; Lahey, 2009; Lysaker et al, 1998), and the effect on quality of life persists when controlling for symptoms and sociodemographic factors (Boyette et al, 2014b, 2014a; Kentros et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroticism questionnaires are often used to assess an individual's stress sensitivity, and it has been shown that people with schizophrenia report higher levels of neuroticism (Horan et al 2005). Moreover, neuroticism scores have been associated with positive symptoms (Lysaker et al 2003 ;Barrantes-Vidal et al 2009) and with increased risk for psychosis at both the clinical and subclinical level (van Os & Jones, 2001 ;Krabbendam et al 2002). In one experimental study using a speech stress task, higher levels of trait arousability (an individual's emotional and physiological reactivity to novel events) were found to be associated with positive and affective symptoms (Dinzeo et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, RS increases with greater general psychopathology in individuals at risk for psychosis (A. P. Morrison et al, 2006) and is greater-than-normal in individuals with schizotypal personality disorder (Torgersen et al, 2002). Research clearly indicates that general anxiety (neuroticism) relates to schizotypy (Ettinger et al, 2005;Barrantes-Vidal et al, 2009), where the relation is influenced by both genetic and environmental factors (Macare et al, 2012). Furthermore, the presence of RS across the psychosis continuum (Kwapil, Brown, Silvia, Myin-Germeys, & Barrantes-Vidal, 2012; A. P. Morrison et al, 2006;Torgersen et al, 2002) might be such that the RS-positive schizotypy association is strengthened by anxiety (Kwapil et al, 2012).…”
mentioning
confidence: 99%